Design of a low cost coin acceptor for vending machine - Ho Chee Leong, Richmond Chris; Zulkipli, Muhammad; Shaari, Muhammad Farid (2021)
Coin acceptor is a device that receive and identifies the validity of the coin. It works by analyzing the coin it received based on its mass, size, diameter, thickness, metal composition, and then sends an appropriate signal through the output connection. However, the cost of purchasing the device is rather high compare to self-fabricate where the current surveys on online shows that the device will cost around RM150-300. This cost is consider high for SME who just planning to start their vending machine business. Therefore, the alternative to come out with a design for a low cost coin acceptor for the vending machine had been done. To make sure the cost will not be high the scope of the project has been determine where the device is designed to only accept the second series version of RM0.50 which is 27 mm in diameter. In this project, the design is produced by using Solidworks software and the coin identification mechanism was designed by integrating the like of sensors, actuators and microcontroller which is the basic component of a coin acceptor. To further reduce the cost a new mechanism of a rejection hole were introduced to replace and eliminate number of sensor used. The expected cost to fabricate the design was expected to be around RM138 and further cost reduction can be done with further research on reducing the product component.